2019
DOI: 10.1109/tcyb.2017.2778799
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the Volume of the Left Ventricle From MRI Images Using Deep Neural Networks

Abstract: Abstract-Segmenting human left ventricle (LV) in magnetic resonance imaging (MRI) images and calculating its volume are important for diagnosing cardiac diseases. In 2016, Kaggle organized a competition to estimate the volume of LV from MRI images. The dataset consisted of a large number of cases, but only provided systole and diastole volumes as labels. We designed a system based on neural networks to solve this problem. It began with a detector combined with a neural network classifier for detecting regions … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…As is reported in [23], registration takes at least 20 seconds per patient using GPUs and typically tens of minutes per patient using CPUs. Learning based RoI localization decouples RoI localization from prior knowledge [24][25][26][27][28]. Some of the related practices [24,29] ex-tract region proposals using external modules such as Selective Search [30] or Multiscale Combinatorial Grouping (MCG) [31], which are also well-known speed bottlenecks as is pointed out in [32] and replacing them with RPN accelerated a network from 0.5 fps to 5 fps.…”
Section: Introductionmentioning
confidence: 99%
“…As is reported in [23], registration takes at least 20 seconds per patient using GPUs and typically tens of minutes per patient using CPUs. Learning based RoI localization decouples RoI localization from prior knowledge [24][25][26][27][28]. Some of the related practices [24,29] ex-tract region proposals using external modules such as Selective Search [30] or Multiscale Combinatorial Grouping (MCG) [31], which are also well-known speed bottlenecks as is pointed out in [32] and replacing them with RPN accelerated a network from 0.5 fps to 5 fps.…”
Section: Introductionmentioning
confidence: 99%
“…However, in order to increase the robustness and accuracy, most of the mathematical segmentation requires a prior knowledge, problematic assumptions, or user interaction [13][14][15]. e representative methods consist of CNN [4,5,17], sliding window [18][19][20], Full Connected Network [6,[21][22][23], U-Net [7,8,24], and 3D Convolution [25][26][27].…”
Section: Segmentation Based On Mathematical Calculationsmentioning
confidence: 99%
“…In recent years, Cardiac Magnetic Resonance (CMR) has become a crucial imaging modality in clinical cardiology practice due to its high signal-to-noise ratio, noninvasive imaging to cardiac chambers, no need for geometric assumptions, and great vessels [1,2]. Although much effort has been devoted to left ventricle quantification over the last several decades [2][3][4][5][6][7][8], it remains in the research stage and the reported algorithms are still not robust and flexible enough to support clinic practice due to the complexity of medical imaging. erefore, left ventricle quantification is still acknowledged as a challenge with much room for improvements in robustness, flexibility, and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown in the paper that this configuration performed better than other simpler u-nets in terms of Dice. In their article Liao et al [137] detected the Region of Interest (ROI) containing LV chambers and then used hypercolumns FCN to segment LV in the ROI. The 2-D segmentation results were integrated across different images to estimate the volume.…”
Section: A Magnetic Resonance Imagingmentioning
confidence: 99%